Factors influencing vocational teachers’ e-Learning adoption: A technology acceptance model approach - Roni Eka Rahmat; Samsul Hadi; Iis Elfa Syafmaini; Utari Akhir Gusti; Afdal Luthfi; Aprilla Fortuna (Jurnal Pendidikan Vokasi, 2025)
The rapid expansion of digital learning environments has encouraged schools to integrate e-learning into teaching practices. However, many vocational teachers still show uneven levels of adoption, indicating that the factors shaping their willingness and actual use of e-learning require deeper investigation. This study examines the determinants of vocational teachers’ e-learning adoption using the Technology Acceptance Model (TAM), focusing on the roles of perceived usefulness (PU), perceived ease of use (PEOU), behavioral intention (BI), and actual use (AU). A quantitative survey was administered to 118 vocational high school teachers, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that PEOU significantly influences both PU and BI, while PU also exerts a positive effect on BI. Furthermore, BI demonstrates a strong and significant effect on AU, mediating the relationships between PU, PEOU, and AU. Overall, the model explains a substantial proportion of variance in teachers’ behavioral intention and actual use of e-learning. These results confirm the robustness of TAM in vocational education contexts and highlight that teachers are more likely to use e-learning when they perceive it as easy, useful, and aligned with their instructional needs. Practically, the study suggests that vocational schools should strengthen digital literacy training, provide technical support, and design user-friendly platforms to enhance teachers’ confidence and motivation. At the policy level, establishing clear digital competence standards may foster sustainable e-learning adoption across vocational institutions.